2012 IEEE Conference on Computer Vision and Pattern Recognition 2012
DOI: 10.1109/cvpr.2012.6247885
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the articulated motion of two strongly interacting hands

Abstract: We propose a method that relies on markerless visual observations to track the full articulation of two hands that interact with each-other in a complex, unconstrained manner. We formulate this as an optimization problem whose 54-dimensional parameter space represents all possible configurations of two hands, each represented as a kinematic structure with 26 Degrees of Freedom (DoFs). To solve this problem, we employ Particle Swarm Optimization (PSO), an evolutionary, stochastic optimization method with the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
212
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(216 citation statements)
references
References 18 publications
0
212
0
2
Order By: Relevance
“…Moreover, a common approach for learning both the interaction that involves objects (Oikonomidis et al, 2013;Kyriazis and Argyros, 2014) and object affordances (Koppula et al, 2013;Koppula and Saxena, 2014), from RGB-D data, is to utilize a tracking algorithm for tracking the hand movement of a human user. The learning method that we have suggested in this work is solely based on the tracked movements of object entities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a common approach for learning both the interaction that involves objects (Oikonomidis et al, 2013;Kyriazis and Argyros, 2014) and object affordances (Koppula et al, 2013;Koppula and Saxena, 2014), from RGB-D data, is to utilize a tracking algorithm for tracking the hand movement of a human user. The learning method that we have suggested in this work is solely based on the tracked movements of object entities.…”
Section: Discussionmentioning
confidence: 99%
“…(4)) is performed based on Particle Swarm Optimization (PSO) [19] which is a stochastic, evolutionary optimization method. It has been demonstrated that PSO is a very effective and efficient method for solving other vision optimization problems such as head pose estimation [23], hand articulation tracking [22] and others. PSO achieves optimization based on the collective behavior of a set of particles (candidate solutions) that evolve in runs called generations.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…Indeed, rather few works explicitly model the physical collision between objects. Oikonomidis (2012) tracks two interacting hands with Kinect input, introducing a penalty term measuring the inter-penetration of fingers to invalidate impossible articulated poses. Both Oikonomidis et al (2011b) and Kyriazis and Argyros (2013) track a hand and moving object simultaneously, and invalid configurations similarly penalized.…”
Section: Related Workmentioning
confidence: 99%